2018
DOI: 10.15252/emmm.201708741
|View full text |Cite
|
Sign up to set email alerts
|

Soluble stroma‐related biomarkers of pancreatic cancer

Abstract: The clinical management of pancreatic ductal adenocarcinoma (PDAC) is hampered by the lack of reliable biomarkers. This study investigated the value of soluble stroma‐related molecules as PDAC biomarkers. In the first exploratory phase, 12 out of 38 molecules were associated with PDAC in a cohort of 25 PDAC patients and 16 healthy subjects. A second confirmatory phase on an independent cohort of 131 PDAC patients, 30 chronic pancreatitis patients, and 131 healthy subjects confirmed the PDAC association for MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 59 publications
(92 reference statements)
2
43
0
Order By: Relevance
“…MMP7 and MMP26 are the only two members of the matrilysin subfamily. A large number of studies have compared MMP7 expression in PDAC patients with pancreatitis patients and/or healthy controls and have consistently shown that MMP7 levels are elevated in PDAC patients (Table 1) [34][35][36]54,69,91,[97][98][99][100][101][102][103][104]. More importantly, MMP7 levels correlate with metastasis and/or survival in most, but not all, studies.…”
Section: Matrilysins In Pdacmentioning
confidence: 99%
“…MMP7 and MMP26 are the only two members of the matrilysin subfamily. A large number of studies have compared MMP7 expression in PDAC patients with pancreatitis patients and/or healthy controls and have consistently shown that MMP7 levels are elevated in PDAC patients (Table 1) [34][35][36]54,69,91,[97][98][99][100][101][102][103][104]. More importantly, MMP7 levels correlate with metastasis and/or survival in most, but not all, studies.…”
Section: Matrilysins In Pdacmentioning
confidence: 99%
“…Six-to eight-week old female C57BL/6 mice (Charles River Laboratories, Lecco, Italy) were maintained under specific-pathogen-free conditions, with constant temperature and humidity, and handled using aseptic procedures. FC1199 cells (5 × 10 4 ) were implanted orthotopically in the pancreas as described [18]. Peptides were administered i.p.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Tumors were collected, fixed in 10% phosphate-buffered formalin, embedded in paraffin, and cut into 4 µm-thick sections. Sections were stained with Hematoxylin and Eosin (H&E) and Sirius red as described [18]. For immunohistochemical analysis of the tumor vasculature, anti-mouse CD31 antibody SZ31 (Dianova GmbH, Hamburg, Germany) followed by biotin-conjugated goat anti-rat IgG antibody (Vector Laboratories, Burlingame, CA, USA) and streptavidin-alkaline phosphatase conjugate were used [18].…”
Section: Histological and Immunohistochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous potential biomarkers have been identi ed, including b7-h4, MUC13. However, none has been able to precisely predict the presence and outcomes of the disease, which is crucial in guiding the course of treatment of PAAD patients [8,9].…”
Section: Introductionmentioning
confidence: 99%